Effect of Fiber Orientation Angle on Stress Intensity Factor of Composite Plate Using Extended Finite Element Method (XFEM) - Kahyoosh, Maha Sabah; Laftah, Rafil Mahmood; Nassar, Ameen Ahmed (Basrah Journal for Engineering Sciences, 2022)
This paper presents the effect of fiber orientation angle on the stress intensity factor SIF for carbon epoxy composite plates with single-edge, center, and inclined cracks of varying lengths under tensile load. The stress intensity factor and shape factor were calculated individually for each case, with nine different fiber orientation angles computed using the extended finite element method XFEM concepts. It is found the stress intensity factor increases with increasing crack lengths while the shape factor decreases. In the case of single edge cracks, the SIF increases in the average value reached (173 %) for composite plates with different fiber orientation angles, while in the case of the center crack, the average value of SIF reaches (81 %). It was observed in this study that the increases in stress intensity factor and the decreases in the shape factor with different crack lengths were more stable in the composite plate with a fiber orientation angle of 75°. The higher values of SIF at an angle of 75° are because of the high probability of fiber slippage at 75° due to induced shear stresses in addition to the tensile stresses at the fiber-matrix interface. As a result, the crack tip has a high-stress intensity factor.